2005
DOI: 10.1175/jcli3423.1
|View full text |Cite
|
Sign up to set email alerts
|

The Interannual Variability of the Onset of the Maize Growing Season over South Africa and Zimbabwe

Abstract: Subsistence farmers within southern Africa have identified the onset of the maize growing season as an important seasonal characteristic, advance knowledge of which would aid preparations for the planting of rain-fed maize. Onset over South Africa and Zimbabwe is calculated using rainfall data from the Climate Prediction Center (CPC) Merged Analysis of Precipitation (CMAP) and the Computing Center for Water Research (CCWR). The two datasets present similar estimates of the mean, standard deviation, and trend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
112
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 37 publications
11
112
1
Order By: Relevance
“…The 500 hPa height ( Figure 6) and MSLP (not shown) anomalies imply that early onset may be associated with a strengthening and southward shift of the South Atlantic and South Indian anticyclones and increased ridging southeast of South Africa during the September-November prior to the main rainy season. Using a self-organising map approach, Tadross et al (2005) also found ridging southeast of South Africa for early onset seasons calculated for Zimbabwe. Relative convergence (divergence) (Figure 7) is seen over the central interior, the eastern seaboard of South Africa and Limpopo (large areas of the South West Indian Ocean) consistent with increased ridging southeast of South Africa.…”
Section: Onset Dates Of the Rainy Seasonmentioning
confidence: 89%
“…The 500 hPa height ( Figure 6) and MSLP (not shown) anomalies imply that early onset may be associated with a strengthening and southward shift of the South Atlantic and South Indian anticyclones and increased ridging southeast of South Africa during the September-November prior to the main rainy season. Using a self-organising map approach, Tadross et al (2005) also found ridging southeast of South Africa for early onset seasons calculated for Zimbabwe. Relative convergence (divergence) (Figure 7) is seen over the central interior, the eastern seaboard of South Africa and Limpopo (large areas of the South West Indian Ocean) consistent with increased ridging southeast of South Africa.…”
Section: Onset Dates Of the Rainy Seasonmentioning
confidence: 89%
“…Diurnal temperature ranges vary regionally between 10 and 14°C (Griffiths 1972). Rainfall during the major cropping season starts in southern Mozambique with the advection of moisture onshore by mid-latitude ridging systems (Tadross et al 2005). This can occur as early as September, but the systems can be sporadic, often leading to long early season dry spells.…”
Section: Mozambique Climate and Maize Productionmentioning
confidence: 99%
“…The RFE2 drives a number of monitoring products used in the food security analysis such as the standardized precipitation index (SPI) and water requirement satisfaction index (WRSI). The ability to use RFE2 for quantitatively monitoring food security in Africa is affirmed in literature (Tadross et al 2005;Verdin et al 2005;Sawunyama and Hughes 2008;Tadesse et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…This research uses the technique developed in West Africa (AGRHYMET 1996) and reinforced in WRSI literature (Verdin and Klaver 2002;Senay and Verdin 2003), defining SOS as the first dekad receiving 25 mm of rainfall, followed by two dekads summing to 20 mm. While there may be local deviations from this as a viable SOS, it is a widely supported approximation (Tadross et al 2005;Tadesse et al 2008;Funk and Budde 2009;Crespo et al 2011;Harrison et al 2011).…”
Section: Introductionmentioning
confidence: 99%